Self-assessment system and understanding of tax regulations in increasing individual taxpayer compliance - Rumahorbo, Sri Murni; Rinendy, Jhon (Universitas Wiralodra, 2023)
The research aims to increase individual taxpayer compliance. To answer this aim, this research uses descriptive statistical quantitative data. The data collection in this research was obtained from questionnaires obtained from respondents by distributing them using G-form and distributed to individual taxpayers who have NPWPs in several neighborhood associations, or community associations spread across Rawamangun. The total sample was 74 respondents. Furthermore, data analysis in this research was carried out with the help of the SPSS 22 application using instrument tests, classical assumption tests, and multiple linear regression tests. The research results show that the self-assessment system and an understanding of tax regulations have a crucial role in increasing individual taxpayer compliance. In addition, this research concludes that the self-assessment system significantly affects taxpayer compliance and knowledge of tax regulations. Therefore, this research provides recommendations, namely the importance of education regarding tax regulations, and taxpayers need to be provided with clear information regarding their tax obligations.